1973
DOI: 10.1530/jrf.0.0320429
|View full text |Cite
|
Sign up to set email alerts
|

The Contraceptive Action of the Copper Iud in the Rat

Abstract: Summary. Experiments are described that were designed to show the time and site of the contraceptive action of an intrauterine copper device in the rat. The IUD had no effect on fertilization. Progressively fewer embryos survived, the later the device was removed during the afternoon and evening of the 4th day of pregnancy. The presence of the IUD for the first few hours only of embryonic life completely suppressed implantation, causing death of the embryos. Exposure of the pseudopregnant uterus to copper for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

1974
1974
1990
1990

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…The results of this study in the rabbit contrast with observations on the rat (Chang et al, 1970;Webb, 1973), in which intrauterine copper, inserted on Day 1 of pseudopregnancy (Day 0 = oestrus), not only fails to elicit deciduali¬ zation but inhibits the response to subsequent uterine trauma. However, this is consistent with the fact that premature insertion of a thread into the rat uterus inhibits the response to subsequent trauma (De Feo, 1967), whereas there is some evidence that in the rabbit this manoeuvre facilitates deciduoma produc¬ tion (Marston & Chang, 1969).…”
contrasting
confidence: 94%
“…The results of this study in the rabbit contrast with observations on the rat (Chang et al, 1970;Webb, 1973), in which intrauterine copper, inserted on Day 1 of pseudopregnancy (Day 0 = oestrus), not only fails to elicit deciduali¬ zation but inhibits the response to subsequent uterine trauma. However, this is consistent with the fact that premature insertion of a thread into the rat uterus inhibits the response to subsequent trauma (De Feo, 1967), whereas there is some evidence that in the rabbit this manoeuvre facilitates deciduoma produc¬ tion (Marston & Chang, 1969).…”
contrasting
confidence: 94%
“…It has been suggested that copper has a direct effect upon the embryo before implantation . The continued presence of copper in the uterus of rats (Chang ¡fcTatum, 1970;Webb, 1973) and rabbits (Polidoro et al, 1974) results in a reduction in the number of recoverable embryos or implantation sites. Evidence of an embryocidal effect of copper has also been obtained from studies of the effect of cupric ions and copper metal in vitro (Brinster & Cross, 1972;Naeslund, 1972;Whitting¬ ham, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that the primary mechanism of action of the Cu-IUD is its ovotoxic effect (Webb, 1973 ;Abraham et al, 1974), perhaps a direct toxic effect of copper ions or an indirect effect due to intraluminal pus, or both. On this basis, in our study the pyometra produced by the copper would alone seem more than adequate to account for the antifertility effect observed, and there is no need to postu¬ late any more subtle action on the endometrium (Segal & Atkinson, 1973), although such an action cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%